Toxoplasma gondii, endothelial cells and schizophrenia: is it just a barrier matter? - Cavalari, Victoria Cruz; Cardoso Garcia, Luiz Fernando; Massuda, Raffael; Albrecht, Letusa (Frontiers in Cellular and Infection Microbiology, 2025)
Toxoplasma gondii is an obligatory intracellular parasite responsible for causing toxoplasmosis. It is estimated that approximately one-third of the world’s population has positive serology for toxoplasmosis. Acute T. gondii infection often results in subtle symptoms because of its nonspecific nature. Owing to immune pressure, parasites tend to encyst and persist in different tissues and organs, such as the brain, chronicling the infection. While most chronically infected individuals do not develop significant symptoms, the parasite can affect the central nervous system (CNS), leading to symptoms that range from dizziness to behavioral changes. To reach the CNS, parasites must overcome the blood–brain barrier, which is composed primarily of endothelial cells. While these cells are typically efficient at separating blood elements from the CNS, in T. gondii infection, they not only permit parasitic colonization of the CNS but also contribute to an inflammatory profile that may exacerbate previously established conditions at both the local CNS and systemic levels. An increasing body of research has demonstrated a potential link between the CNS, infection by T. gondii and the cellular or humoral response to infection, with the worsening of psychiatric conditions, such as schizophrenia. Therefore, continually advancing research aimed at understanding and mitigating the relationship between parasitic infection and schizophrenia is imperative.